Linear regression technique for improvement of feet position estimation during standing balance using a cane with millimeter wave radar - Fernandez, Ibai Gorordo; Kitagawa, Kodai; Abdul Rahman, Kawthar; Che Soh, Azura; Alpha, Agape Gopalai; Ahmad, Siti Anom; Wada, Chikamune (Universiti Putra Malaysia Press, 2020)
It is estimated that one in three seniors fall at least once a year. Falls are a global problem for the elderly that affects their quality of life and poses a great risk. In our research, we are trying to develop a system that could prevent falls by estimating the fall risk in real time. The system would measure the balance of the user by measuring the position of the Center of Gravity inside the Base of Support. In our previous research, we presented a system with a millimeter wave radar attached to a cane to measure the area of the Base of Support. However, the obtained results for the foot position estimation error were significantly worse than similar studies. One of the reasons was that the sensor was not really estimating the position of the feet but the position of the lower legs. Therefore, in this research we present a correction model to improve the feet position estimation. The proposed model was able to reduce the foot position estimation RMSE from 54 mm down to 34 mm, which is closer to the results of other similar studies measuring the position of the feet.